Obligations of beneficiary and arising rights in the insurance contract – A Comparative, analytical study – - Hulaiel, Muneer Ali (Journal of Economic, Administrative and Legal Sciences, 2021)
In this study, the obligations of the beneficiary and his rights to the insurance contract were dealt with as an impact on the insurance contract, which is of interest at present, which is not comparable to any different types and forms of insurance, indicating that the legislation in question has intervened and imposed some types of legal provisions, as in the case of insurance from liability arising from traffic accidents.This is due to the mandatory insurmountably of each vehicle owner, given the risks caused by the damage caused by vehicle accidents and the financial consequences of those responsible for these damages and the aim of this study to address the issue by analysis and comparison between Jordanian civil law, UAE civil transaction law and Egyptian civil law. We referred to some special legislation on compulsory car accident liability insurance.One of the most notable findings is that comparative legislation did not include regulatory provisions for the insurance contract to the extent commensurate with its nature and importance.It is recommended is that there must be a modern, ideal insurance law instead of relying on general rules.
Keywords: insurance contract; liability; compulsory vehicle insurance system; compensation; damage